Workshop Membangun Pelayan Publik Yang Anti Korupsi - Ridianto, Ridianto; Ilham, Debi Afriansyah; Khofifah , Devia; Munthe, Abdul Kholik; Junius, Wiwin (Universitas Dehasen Bengkulu, 2021)
The workshop